Hydrocracking of long paraffins over Pt-Pd/WO3-ZrO2 in the presence of sulfur and aromatic impurities - Busto, Mariana (2013)
The hydrocracking of long paraffins in the presence of sulfur and aromatic impurities using Pt–Pd/WO3–ZrO2 was assessed. The catalysts were tested for n-hexadecane hydrocraking in the presence and absence of several poisons, benzothiophene, quinolein, carbon disulfide, benzene, and naphthalene. At small impurity levels, aromatics are beneficial for the hydrocracking of long paraffins because they increase the liquid yield and reduce the cracking to light gases. Sulfur compounds were strong poisons of the activity. Benzothiophene was the strongest, producing the highest decline in activity and being more strongly chemisorbed than basic quinolein. Sulfur poisoning drastically affected the hydrocracking activity, indicating that acid isomerization cracking on WO3–ZrO2 follows a bifunctional mechanism with a big influence of the metal function. Incorporation of Pd to Pt/WO3–ZrO2 reduced the sulfur poisoning, with Pt–Pd (3:1)/WO3–ZrO2 being the best catalyst for stable hydrocracking of long paraffins in the presence of sulfur. This catalyst retained most of the activity of the Pt/WO3–ZrO2 parent material while being less affected by sulfur.